2008
DOI: 10.2320/matertrans.mer2008098
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Calibration Scheme for the EDM Hole-Drilling Strain Gage Method for the Measurement of Residual Stress in Ferrous Materials

Abstract: Recent studies revealed that EDM hole-drilling strain gage method is applicable for the measurement of residual stress in materials with higher hardness and toughness. However, the metallurgical transformation layer formed on the wall of the hole induces an additional stress and therefore generates a measurement error. Usually this error can be calibrated by estimating and reducing the hole-drilling induced extra stress, IS . However, the value of IS is highly sensitive to the EDM parameters. Accordingly, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…As a result, some form of calibration procedure is required to compensate for this additional residual stress such that an accurate assessment of the original residual stress within the workpiece can be obtained. In previous studies by the current group, it was shown that the value of the hole-drilling induced stress is independent of the original stress intensity within the component, and as a result, the measured value of the residual stress can be calibrated by subtracting the value of the residual stress induced by a hole-drilling operation in a stress-free specimen of the equivalent type [8,9]. However, this technique, while undeniably effective, incurs considerable time, manpower, and material costs.…”
Section: Introductionmentioning
confidence: 97%
“…As a result, some form of calibration procedure is required to compensate for this additional residual stress such that an accurate assessment of the original residual stress within the workpiece can be obtained. In previous studies by the current group, it was shown that the value of the hole-drilling induced stress is independent of the original stress intensity within the component, and as a result, the measured value of the residual stress can be calibrated by subtracting the value of the residual stress induced by a hole-drilling operation in a stress-free specimen of the equivalent type [8,9]. However, this technique, while undeniably effective, incurs considerable time, manpower, and material costs.…”
Section: Introductionmentioning
confidence: 97%